GENERATING DSS GRAPH BY EDGE SUBDIVISION AND EDGE CONTRACTION - M. YAMUNA; K. KARTHIKA (Innovare Journal of Engineering and Technology, 2014)
A graph G is said to be domination subdivision stable ( DSS ) if g ( Gsd uv ) = g ( G ), for all u, v ÃŽ V ( G ), u adjacent to v. In this paper we have provided two methods of obtaining a DSS graph from a non DSS graph.